Poppy Muddlepup's daring rescue - Daisy Meadows (Orchard Books, 2014)
Welcome to a magical world where animals talk and play - just like you and me! In this bumper special, Lily and Jess meet Poppy Muddlepup. When the mean witch Grizelda puts a spell on Poppy's twin brother Patch, the girls know they're in for one of their most exciting adventures yet!